Overweight and Obesity among Female Teachers in State Schools in Sri Lanka - Damitha Uyangoda; Phataraphon Markmee (Jurnal Kesehatan Masyarakat, 2025)
Overweight and obesity, marked by excessive body fat, significantly contribute to chronic diseases, including non-communicable diseases, leading to over 4 million deaths globally. In Sri Lanka, obesity is highly prevalent among female teachers, necessitating an exploration of associated factors for effective risk reduction. This study examined the prevalence and determinants of overweight and obesity among female teachers in Sri Lankan state schools. A cross-sectional study was conducted among 328 teachers in the Matara educational zone, utilizing a multistage sampling technique. Data on socio-demographic, lifestyle, work, environmental, and medical factors were collected. Physical activity was assessed using the Global Physical Activity Questionnaire (GPAQ) and analyzed with MET values. A validated questionnaire (IOC: 0.67–1.00, Cronbach’s alpha: 0.70–0.84) ensured reliability, and binary logistic regression identified associated factors. The average age was 44.17 years, with 86.28% married. Based on Asian BMI standards, 73.2% were overweight or obese. Insufficient physical activity (71.04%) and poor dietary habits (58.54%) were the most common issues. Major risk factors included low physical activity (AOR = 7.14; 95% CI: 3.78–13.01) and poor dietary habits (AOR = 1.91; 95% CI: 1.03–3.54). Interventions should promote lifestyle behavior, including physical activity and healthier diets, while policies must raise awareness of obesity-related health risks.